A Novel Tetrameric Venom Protein, Agglucetin from Agkistrodon acutus , Acts as a Glycoprotein Ib Agonist - Wang, Wen-Jeng; Huang, Tur-Fu (Thrombosis and Haemostasis, 2001)
A novel platelet agglutination inducer, agglucetin, was purified from the Formosan Agkistrodon acutus snake venom. It migrated as a single band with an apparent molecular mass of 58.8 kDa and two distinct bands of 16.2/14.5 kDa under non-reducing and reducing conditions by SDS-PAGE, respectively. Further confirmed by FPLC, electrospray ionization mass spectrometry and 2D-PAGE, native agglucetin exists as a tetramer composed of disulfide-linked α1, α2, β1 and β2 subunits. Partial N-terminal sequence of agglucetin subunit showed a high degree of homology to those of C-type lectin-like glycoprotein (GP) Ib binding proteins. Functional studies showed that agglucetin, in the absence of von Willebrand factor (vWF), dose-dependently induced platelet agglutination and caused a negligible elevation of intracellular Ca+2 mobilization and thromboxane B2 formation in human platelet suspensions. Anti-GP Ib monoclonal antibodies (mAbs), AP1 or LJ-Ib1, specifically inhibited agglucetin-induced platelet agglutination in a dose-dependent manner. However, EDTA, arietin (a long chain RGD-containing disintegrin), 7E3 (an anti-GP IIb/IIIa mAb), heparin, hirudin, PGE1, or indomethacin exhibited no inhibitory effect on agglucetin-induced platelet agglutination. Furthermore, flow cytometric analysis revealed that FITC-agglucetin dose-dependently bound to human formalin-fixed platelets in a saturable manner, and its binding was specifically blocked by anti-GP Ib mAb. It is concluded that agglucetin, acts specifically on an epitope of platelet membrane GP Ib overlapping with that of AP1, causing platelet agglutination in a Ca+2- and GP IIb/IIIa-independent manner.
Keywords: C-type lectin-like venom proteins; Agkistrodon acutus; platelet agglutination; von Willebrand factor; glycoprotein Ib agonist